Individualized Care in Nursing Homes Before and After the COVID-19 Pandemic - García-Camacha Gutiérrez, Aurora; García-Camacha Gutiérrez, Irene; Suhonen, Riitta; Rodríguez-Martín, Beatriz (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background: Individualizing care is the essence of nursing, and its benefits have been extensively proven in older people. The changes arisen during the COVID-19 pandemic may have affected it. The aim of this study is to analyze the changes produced in the perceptions about the individualization of care, quality of life, and care environment of elderly people living in long-term care centers before and after the pandemic.
Methods: A prospective cross-sectional observational study was carried out. For data collection, the Individualized Care Scale-patient, the EuroQol-5D scale, and a reduced version of the Sheffield Care Environment Assessment Matrix test were used, and a statistical analysis was performed.
Results: A total of 177 people participated in the study, with 87 pre-COVID-19 and 90 post-COVID-19, 62.7% of whom were women. The average age was 83.3 years. General activities of the individualized care obtained medians of 4, 2.5, and 3 (out of 5) in clinical situation, personal life situation, and decisional control dimensions, respectively, and no substantial change was observed pre- and post-pandemic. Nevertheless, 10 out of 17 items related with the maintenance of individuality in the last shift were higher rated after COVID-19. They are mainly related to the feelings and needs of care, daily life activities, and the expression of opinions. The median of all items was 3 despite the improvement observed after the pandemic. Residents scored an average of 6.47 points (out of 10) in the life quality self-evaluation and were satisfied with the care environment (94%). Patients with higher life quality and adherence to their environment perceived better care. Conclusions: Although slight improvements were observed in the individualized care after the pandemic, the obtained results revealed that there is still room for improvement. Particularly, it is necessary to develop strategies aimed at motivating the family participation or providing individual spaces in the residences.